THE IMAGE OF GOD ACCORDING TO THOMAS AQUINAS - Juwinner Dedy Kasingku (Universitas Pahlawan Tuanku Tambusai, 2022)
In God's likeness and image, the man was made. But the likeness of God seemed to diminish once man committed sin. Man, nevertheless, continues to bear God's likeness and image. One of the key leaders in church history, Thomas Aquinas, tries to clarify what this likeness and image of God signify. The Bible offers a perspective on this aspect of God's likeness and image. The Seventh-Day Adventist doctrines offer an explanation for it that is consistent with the biblical perspective. In the end, it was discovered that while Adventist teachings are in line with the Bible and hold that the image of God can be found in a broader view, namely in the physical, mental, and spiritual, as opposed to Thomas Aquinas's argument that it can only be found in human intellect and understanding. Keywords: image, likeness, Thomas Aquinas